Development Of Cassava-Based Rice Analogue And The Study On Its Physicochemical Properties - Liu, Chiew Yen (Universiti Sains Malaysia, 2021)
Rice analogue has been developed as one of the carbohydrate sources of staple food. It is made from non-paddy carbohydrate source such as cassava, corn and sorghum. Commercial white rice is rich in carbohydrate while low in protein, fiber and other essential minerals and it is found to associate with Type 2 diabetes. Therefore, this study was aimed to develop cassava-based rice analogue which can act as healthier alternative to commercial white rice. The effect of ratio of modified cassava flour to rice flour and percentage of cassava leaves on the physicochemical properties of cassava-based rice analogue was studied. Samples developed were analyzed based on proximate composition, amylose content, cyanide content, texture profile analysis, colour, swelling power, water absorption capacity and morphology. Results showed that both ratio of modified cassava flour to rice flour and percentage of cassava leaves addition had significant effect on the physicochemical properties of cassava-based rice analogue. It was found that RAF 2 (rice analogue formulated with 5:5 in term of ratio of modified cassava flour to rice flour) fortified with 20 % cassava leaves possessed the most desirable properties in term of proximate composition, amylose content and functional properties. It demonstrated better nutrition in term of high level in protein (10.91 ± 0.59 %), fiber (2.14 ± 0.11 %) and amylose content (27.48 ± 0.76 %). It also possessed better functional properties in term of swelling power and water absorption capacity and its texture was resembled to control (rice flour). In term of safety aspect, cyanide content (2.65 ± 0 ppm) was also fulfilled the requirements by WHO indicates that it is safe to be consumed. In a conclusion, rice analogue developed using both cassava roots and leaves can act as healthier alternative to commercial white rice.